Pendampingan pada Komunitas Pelajar Tingkat Dasar Desa Gapluk Bojonegoro dalam Meningkatkan Minat dan Kualitas Membaca - Syihabuddin, Muhammad Arif (Community: Jurnal Pengabdian Kepada Masyarakat, 2023)
This Community Service aims to increase interest and quality of reading among elementary students in Gapluk Village, Bojonegoro. Through a participatory approach, this research involves the student community, teachers, and local communities in the mentoring process. Activities involve reading coaching, procurement of reading materials, and training in creative learning methods. The results of this community service are expected to make a positive contribution to increasing interest in reading and improving the quality of understanding and retention of information among elementary level students. The program is also expected to provide a model for similar efforts in similar communities.